Prevalensi Dan Derajat Infeksi Cacing Endoparasit Penyebab Zoonosis Pada Ikan Kakap Merah (Lutjanus Sanguineus) Di Pasar Tradisional Dan Supermarket Kota Surabaya - Tazakkaa Riesna Indra Puspa (2020)
This study was aimed to know the prevalence and infection rate of zoonotic endoparasite worms in red snapper from wet market and supermarket in Surabaya. The samples used in this research were 90 red snappers that bought from five wet markets and four supermarkets in Surabaya. The samples were macroscopic and microscopically examined to find out the larvae of endoparasite worms. The results showed 48 out of 90 red snappers were infected by the larvae of Anisakis sp., Terranova sp., and Hysterothylacium sp., that found in the gastrointestinal tract and liver. The prevalence of the infected red snappers were about 27% - 100% and the infection rate were 3.5 – 29 larvae per fish. The prevalence and infection rate were as followed Anisakis sp. 42,2% and 4-5 larvae per fish, Anisakidae (Anisakis sp. and Terranova sp.) 10% and 18-19 larvae per fish, while the Anisakis sp. and Hysterothylacium sp. 1,1% and 7 larvae per fish. The most infected site was in the gastrointestinal tract, none of the worms were found in the muscle of the red snappers.